Expert insights on managing harmful algal blooms - Goodrich, Sarah; Canfield, Katherine Nicole; Mulvaney, Kate (Frontiers in Freshwater Science, 2024)
Freshwater harmful algal blooms (HABs) are a global environmental, economic, social, and public health hazard. While there is an increasing understanding of the ecological considerations of HABs, there is limited understanding of human dimensions and management needs. We conducted semi-structured key informant interviews with 28 water managers and researchers to better understand how they perceive current management and to identify future management priorities in regard to HABs. For this study, we interviewed 31 key informants from three regions of the United States (New England, Ohio, and the Mountain West). We solicited insights across aspects of HABs management, including prevention, forecasting, monitoring, response, and communication. Nutrient management was the main consideration for the prevention of HAB events. Key informants noted that forecasting has the potential to be a valuable tool in the future but is not yet accurate enough at a local scale for widespread use. Monitoring was found to be implemented in varying ways across and even within the states and regions, with a need for more funding and standardization. HAB event responses vary greatly from chemical and physical treatments that suppress toxins to no-swim advisories, all with a mix of strengths and weaknesses. Finally, an increase in and improvement of communication efforts was identified as critical for reducing public health risks. These findings provide perceptions of current management practices and future plans while including opportunities to improve current freshwater HAB management efforts.